Entrepreneurial Process: A Case Study of Mithila Thali Restaurant by Chef Santosh Shah - Shah, Binod; Sah, Rajesh Kumar; Sah, Kiran Kumari (Darul Yasin Al Sys, 2024)
This case study explores the entrepreneurial process behind the establishment and growth of Mithila Thali Restaurant, a culinary venture founded by renowned Chef Santosh Shah. Located in the heart of Nepal, Mithila Thali Restaurant has gained significant recognition for its authentic Mithila cuisine, a traditional food heritage from the Mithila region. The study examines the critical stages of the entrepreneurial journey, including opportunity recognition, business planning, resource mobilization, and strategic execution. Through in-depth interviews with Chef Santosh Shah and key stakeholders, along with a comprehensive analysis of business records and market data, the research highlights the challenges and successes encountered during the restaurant's development. Key findings reveal how Chef Shah leveraged his culinary expertise, cultural heritage, and innovative marketing strategies to create a unique dining experience that appeals to both local and international customers. This case study contributes to the broader understanding of entrepreneurial dynamics in the hospitality industry and provides practical insights for aspiring entrepreneurs aiming to navigate the complexities of starting and sustaining a successful restaurant business.